2021
DOI: 10.1021/acsapm.0c01086
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Porous Polymers via a Microgel Intermediate: Green Synthesis and Applications toward the Removal of Pollutants

Abstract: Exploring a synthetic approach to prepare processable hierarchical porous polymers (PPs) is challenging. In the article, a strategic approach is presented, where polymerization (hyperbranching)-induced self-assembly in water leads to the formation of porous microgels (containing both micropores and mesopores), which is followed by spontaneous cross-linking of those intermediate microgels, leading to the formation of PPs. The synthetic process involves simple and green reactions. During this process, hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…25,26 In this context, it was observed that functional amines when embedded within a polarizable network such as polyaromatic amines and polyaminoamides show excellent iodine adsorption ability. [27][28][29][30] However, most of the reported materials demonstrate iodine adsorption ability only in the vapor phase and organic solvents. [31][32][33][34][35][36][37] Materials which show signicant iodine adsorption ability in water, are much less reported.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In this context, it was observed that functional amines when embedded within a polarizable network such as polyaromatic amines and polyaminoamides show excellent iodine adsorption ability. [27][28][29][30] However, most of the reported materials demonstrate iodine adsorption ability only in the vapor phase and organic solvents. [31][32][33][34][35][36][37] Materials which show signicant iodine adsorption ability in water, are much less reported.…”
Section: Introductionmentioning
confidence: 99%
“…The morphological changes of S. aureus and E. coli cells before and after the treatment with PHMB 4 -g-PMS were examined by scanning electron microscopy (SEM, QUANTA 200, Philips-FEI, Holland). Prior to the SEM observation, the bacterial suspension was fixed by 4% paraformaldehyde for 2 h and then dehydrated by ethanol solutions with a range of concentrations (20,40,60,80, 90, and 100%), and at last, the samples were dried by nitrogen and coated with gold for SEM observation.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The 1 H NMR spectra of xanthan and xanthan acrylate were recorded on a Brüker Advance DRX 400 MHz spectrometer (Germany). 1 H NMR spectra were obtained in D 2 O solution. The swelling ratio of the synthetized materials was evaluated by the gravimetric method.…”
Section: General Characterization Techniquesmentioning
confidence: 99%
“…Generally, these are generated by the emission of toxic or greenhouse gases (CO 2 , NO x ), industrial wastewaters containing dyes, oils, heavy metals or organic compounds, and nuclear wastes. [1] All of them have adverse effects on the environment, and can produce risks to human health, [2,3] directly or indirectly influencing food chains. [4] Organic dye solutions are widely used in different domains, such as textile industries, paper production, cosmetics, pharmaceutical or plastic industries.…”
Section: Introductionmentioning
confidence: 99%